Study guides

☆☆

Q: What is the answer for this equation 2x-3 equals x plus 2?

Write your answer...

Submit

Still have questions?

Related questions

your equation is this... 2x3 + 11x = 6x 2x3 + 5x = 0 x(2x2 + 5) = 0 x = 0 and (5/2)i and -(5/2)i

2x3 + 4 = 17 2x3 = 13 x3 = 13 / 2 x = (13 / 2)1/3 x = 521/3 / 2

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

The equation is 2(x) +3= 9. X would equal 3. The equation would now look like this, 2x3+3=9.

There is no single coefficient for that equation, as a coefficient is the number by which any term is multiplied. The coefficients in that equation are 5, 2, 4 and 3.

x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656

The equation is y + 2 = 12.

It is an equation.

The summary equation is the formula equation. Sugar equals alcohol plus carbon dioxide. The formula is C6H12O6 which equals 2 CH3CH2OH plus 2 CO2.

The summary equation is the formula equation. Sugar equals alcohol plus carbon dioxide. The formula is C6H12O6 which equals 2 CH3CH2OH plus 2 CO2.

That word "equals" in there makes it an equation.

No.

People also asked